Reader reception of translation strategies for Li Bai’s “Yu Jie Yuan”: Empirical evidence from a mixed-methods study - Hongjing Chang; Jing Zhao; Yuhao Sun; Huan Ding (PLoS ONE, 2026)
Classical Chinese poetry faces challenges in cross-cultural communication due to differences in rhythm, imagery, and poetic traditions. Although various translation strategies have been proposed, empirical research on how target readers evaluate them remains limited. This study adopted a mixed-methods approach to examine four English translations of Li Bai’s “Yu Jie Yuan”: prose translation, free verse translation, rhymed translation, and literal translation. A total of 403 American audiences were recruited through the Prolific platform and completed an online questionnaire on Qualtrics. The adapted Reader Response Questionnaire (RRQ) covered five dimensions: “content, theme, affective involvement, character behavior, and typology”. Quantitative data were analyzed using t-tests and analysis of variance, while open-ended responses were subjected to qualitative thematic analysis. In addition, four English translations of Li Bai’s “Yu Jie Yuan” were examined through textual analysis. The results showed that among the four strategies compared, rhymed translation was more popular with readers, indicating its potential advantage in balancing meaning and aesthetics. This study provided empirical support for the role of translation strategies in cross-cultural communication. However, since the sample was limited to American audiences, future research should expand to other cultural groups to verify the generalizability of the conclusion.